2014
DOI: 10.1590/s0102-67202014000400014
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transthoracic liver resection

Abstract: IntroductionMinimally invasive laparoscopic liver surgery is being performed with increased frequency. Lesions located on the anterior and lateral liver segments are easier to approach through laparoscopy. On the other hand, laparoscopic access to posterior and superior segments is less frequent and technically demanding.AimTechnical description for laparoscopic transthoracic access employed on hepatic wedge resection.TechniqueLaparoscopic transthoracic hepatic wedge resection on segment 8.ConclusionTransthora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Previous studies have reported cases of TH for malignant liver tumors. 3 6 Compared to the traditional laparoscopic view, a good exposure of segments VII and VIII can be achieved from the diaphragmatic surface after the diaphragm has been transected. Also, there is no need for mobilization of the entire right hemiliver to rotate it for exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported cases of TH for malignant liver tumors. 3 6 Compared to the traditional laparoscopic view, a good exposure of segments VII and VIII can be achieved from the diaphragmatic surface after the diaphragm has been transected. Also, there is no need for mobilization of the entire right hemiliver to rotate it for exposure.…”
Section: Discussionmentioning
confidence: 99%
“…As for those patients with a history of previous upper abdominal surgery or numerous previous abdominal interventions, 4 , 6 there is a high possibility of severe adhesion around the liver and it is difficult to perform IUSO or the Pringle maneuver laparoscopically with a single trocar. Transthoracic-assisted LH might be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Der Vorteil der laparoskopischen roboterassistierten [24]. Andere Arbeitsgruppen berichten von günstigen Ergebnissen bei einer Lagerung in einer "überdrehten" ca.…”
Section: Roboter Und Navigationunclassified
“…Some specialized centers have reported favorable and competitive outcomes of LLR compared to those of open liver resection [3][4][5]. Recently, several reports about single-port LLR, robotic-assisted liver resection, and LLR via video-assisted transthoracic liver resection (VTLR) have been published [6].…”
Section: Introductionmentioning
confidence: 99%